Analysis of TEF Operational Risk Management for Trains and Underground Stations of MRT Jakarta - Aji, Unggul; Santoso, Sugeng (East Asian Journal of Multidisciplinary Research, 2024)
This research analyzes risk management related to "TEF Operations on MRT Jakarta's Underground Trains and Stations" using HIRADC, referencing AS/NZ4360 standards and its derivatives in ISO 31000, as well as root cause analysis such as fishbone and 5 why analysis. The objectives are as follows, identify potential risks due to changes in TEF operations, provide recommendations to mitigate these risks, and establish suitable and safe TEF operational methods for underground trains and stations. The study identified 33 potential risks from changes in TEF operations on MRT Jakarta's underground system. Additionally, 17 managerial actions were recommended to minimize these risks. Manual TEF operations are deemed more suitable since the automated TEF operation poses a high-risk category that requires control.